Computer system design : system-on-chip - Flynn, M. J. (Michael J.), 1934-; Luk, Wayne (Hoboken, N.J. : John Wiley & Sons, 2011)
'The next generation of computer system designers will be less concerned about details of processors and memories, and more concerned about the elements of a system tailored to particular applications. These designers will have a fundamental knowledge of processors and other elements in the system, but the success of their design will depend on the skills in making system-level tradeoffs that optimize the cost, performance and other attributes to meet application requirements. This book provides a new treatment of computer system design, particularly for System-on-Chip (SOC), which addresses the issues mentioned above. It begins with a global introduction, from the high-level view to the lowest common denominator (the chip itself), then moves on to the three main building blocks of an SOC (processor, memory, and interconnect). Next is an overview of what makes SOC unique (its customization ability and the applications that drive it). The final chapter presents future challenges for system design and SOC possibilities.'--
'This book provides a new treatment of computer system design, particularly for System-on-Chip (SOC), which addresses the issues mentioned above'--
Includes bibliographical references and index.
Keywords: Systems on a chip